2016
DOI: 10.1038/srep38963
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of long noncoding RNA and mRNA expression profiles in human macrophages infected with Mycobacterium tuberculosis

Abstract: Macrophages play a crucial role in the control and elimination of invading Mycobacterium tuberculosis (Mtb), and also serve as the major residence for Mtb. However, the interaction between macrophages and Mtb remains to be clearly determined. Although long noncoding RNAs (lncRNAs) have emerged as key regulators in many biological processes, their roles in anti-mycobacterial responses of macrophages remain to be elucidated. Here, we applied microarray analysis to examine lncRNA and mRNA expression profiles in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 45 publications
3
71
0
Order By: Relevance
“…Studies comparing the lncRNA expression in response to different pathogens possessing different virulence mechanisms are missing. However, it was shown that two strains of M. tuberculosis that differ in virulence induced distinct lncRNA expression profiles (Yang X. et al, 2016). Regarding the therapeutic application, lncRNAs are interesting candidates for host-directed therapies which is a new evolving concept to treat bacterial infections such as tuberculosis.…”
Section: Conclusion/outlookmentioning
confidence: 99%
“…Studies comparing the lncRNA expression in response to different pathogens possessing different virulence mechanisms are missing. However, it was shown that two strains of M. tuberculosis that differ in virulence induced distinct lncRNA expression profiles (Yang X. et al, 2016). Regarding the therapeutic application, lncRNAs are interesting candidates for host-directed therapies which is a new evolving concept to treat bacterial infections such as tuberculosis.…”
Section: Conclusion/outlookmentioning
confidence: 99%
“…In addition, they are increasingly being recognized to play significant roles in the biological behaviors of TB infection. For example, Yang et al found aberrant expression of abundant lncRNAs in MTB‐infected macrophages and identified two lncRNAs molecules, MIR3945HG V1 and MIR3945HG V2 , which could potentially serve as the promising diagnostic markers for TB. These findings all indicate that lncRNA signatures and their genetic variants hold the potential to behave as the marker for identification of TB infection.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that as a coactivator of NF‐kB, lincRNA‐Cox2 functions as a regulator of the late phase of the primary immune response via modulation of epigenetic chromatin remodeling . Intriguingly, lincRNA‐Cox2 has been shown to modulate both the activation and the repression of distinct classes of immune genes in innate immune cells …”
Section: Introduction Of Lncrnasmentioning
confidence: 99%
“…40 Intriguingly, lincRNA-Cox2 has been shown to modulate both the activation and the repression of distinct classes of immune genes in innate immune cells. [40][41][42][43] DCs are antigen-presenting cells, and their main function is to process and present antigen material on the cell surface to T cells. 36 The lncRNA lnc-DC is specifically expressed in human DCs, and it was identified by transcriptome chip and RNA-Seq assays.…”
Section: Introduction Of Lncrnasmentioning
confidence: 99%